Evaluation of the predisposing factors and cause of resistance which are associated with ART 1 failure and shifted to ART 2 regime - Singh, Narendra; Varma, R. K.; Giri, Richa; Varma, Punit; Dwivedi, Seema; Kumar, Lalit (International Journal of Advances in Medicine, 2020)
Background: This study is to evaluate the predisposing factors and cause of resistance which are associated with ART1 failure and shifted to ART 2 regime. Methods: This study was conducted in ART plus centre K.P.S. Post Graduate Institute of Medicine (G.S.V.M. Medical College, Kanpur, India) tertiary care teaching hospital (G.S.V.M. Medical College, Kanpur, India). It will be a clinical (assessment with investigation), continuous, longitudinal, prospective and retrospective, observational, single centre hospital-based study at ART Centre, Kanpur, India. All the subjects who were on 1st line ART regime, attended in our centre were screened for treatment failure of based on clinical, immunological and virological criteria as decided by SACEP. Duration of this study was DEC 2016 TO DEC 2018.This study was taking as regime ART2 as TLATV/R, ZLATV/R, TLLP/R and ZLLP/R. Results: In this study there is PL HIV subjects that are considered for ART2 are mostly living in rural area and more are female having less adherence to ART1. Smoking, alcohol and tobacco chewing were also having less adherence to ART and cause resistance to ART1. Conclusions: In this study subjects were having associated with predisposing factor as Alcohalic 53 (45%), Tobacco Chewing 8 (07%), SMOKING 13 (11%). Alcohalic, Tobacco Chewer and Smoker have significant association of predisposing factor for low adherence to ART1 and resistance to ART1 drugs. There is also concluded that females and rural areas subject are having low adherence and cause ART1 failure.